"Open access" growth histories in millipedes (Diplopoda). Issue 1 (January 2018) - Enghoff, Henrik; Jensen, Laura Mark; Mikhaljova, Elena V.
Abstract: A unique pattern of missing defence glands on certain body rings is described for two species of the millipede family Mongoliulidae, order Julida: Ussuriiulus pilifer Golovatch, 1980, and Koiulus interruptus Enghoff et al., 2017. Based on the patterns of missing glands observed in recently collected samples of the two species, numbers of podous and apodous body rings in successive stadia of the postembryonic development can be inferred for each individual millipede, which in turn allows the reconstruction of pathways of anamorphosis in these species. The inferred numbers of body rings in developmental stadia are compared with actual numbers observed on additional samples, including the type series, of U. pilifer . The pattern of missing glands in the two mongoliulid species is compared with the pattern of missing glands typical of the entire millipede order Polydesmida. Graphical abstract: Highlights: A unique pattern of missing defence glands on certain body rings is described for two species of mongoliulid millipedes. The lack of glands is interpreted in terms of the mode of postembryonic development, anamorphosis, of millipedes. By accepting this interpretation, "open access" to the growth history of each individual millipede is provided.